Students’ Cognitive Learning Outcomes In Simple Machine Subjects Through REACT Learning Model - Haris Rosdianto; Umi Hafizah Syahandri; Natcha Mahapoonyanont (STKIP Singkawang, 2020)
This study aims to determine how much improvement in students' cognitive learning outcomes after applying the REACT learning model on simple machine subjects. This type of research is quantitative research in the form of pre-experimental design. The population in this study were all eighth grade students of SMP Negeri 1 Jawai, Sambas Regency, West Kalimantan. The sample in this study were 25 class VIIIC students, determined by the purposive sampling technique. This research begins with the provision of pretest followed by treatment in the form of application of the REACT learning model and ends with the administration of posttest. From the data analysis, it was found that the cognitive learning outcomes of students experienced an increase of 0.44 based on the N-gain equation with the medium category. The recapitulation results from the attitude scale showed that 87% of students stated that they were better able to understand simple machine subjects using the REACT learning model. It can be concluded that the REACT learning model can improve student learning outcomes on simple machine subjects.